Use Innovativeness for New Product Development: A Study on Users of Titan Watches - Unmesha Pal; Subash Vuppala; Dr. D.N. Murthy (International Journal of Engineering and Management Research, 2020)
Developing a new product requires understanding of consumers, conducting ethnography research, empathizing with the customers, finding their needs, looking at pain points . But more importantly, it is the adoption of the product by the consumer at the end of the day which matters. Estimating the product usage and his need satisfaction level is what helps the product to penetrate in market. Use innovativeness involves the use of previously adopted products in novel ways. As conceptualized by Price and Ridgway use innovativeness encompasses five factors: creativity/curiosity, risk preferences, voluntary simplicity, creative re-use and multiple use potential. Use innovativeness is measured by above scales and a conceptual model of post adoption process is developed. Understanding, the technology adaption life cycle by grouping consumers into Innovators, Early Adaptors, Early Majority, Late majority and Laggards, helps us strike a fine relation between product developed according to its use innovativeness and the stage of technology adoption cycle your product will mostly fall under. The conceptual model is then clubbed with framework for technology adaption cycle which will be useful for companies mainly product based, to understand its target consumers and the target market in hitting with highest probability of success. Companies looking at pivoting a product when the product doesn’t work in the market, is a painful task. Killing a product and it’s usage involves lot of time, effort and money. Developing a product understanding one’s target consumers and looking at their probable adoption is a difficult relation to strike. The Study and Analysis developed here after research of consumers and their use innovativeness in target segment helps us to put the product in right market, at right time and with right adoption purpose based on user innovativeness and will have a future scope of arriving at a framework that can help companies to launch a new product.